2022
DOI: 10.1021/acsami.2c13367
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Mesoporous CuO–CeO2 Catalysts for NH3-SCR Applications Guided by Multiple In Situ Spectroscopies

Abstract: Efficient nontoxic catalysts for low-temperature NH3 selective catalytic reduction (NH3-SCR) applications are of great interest. Owing to their promising redox and low-temperature activity, we prepared CuO–CeO2 catalysts on a mesoporous SBA-15 support using targeted solid-state impregnation (SSI), guided by multiple in situ spectroscopy. The use of template P123 allowed dedicated modification of the surface properties of the SBA-15 matrix, resulting in a changed reactivity behavior of the metal precursors duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…It can be clearly found that the weight loss of complete decomposition for the mixed component of KIT-6 and Cr(NO 3 ) 3 is 448.8 °C, which is slightly higher than that of pure Cr(NO 3 ) 3 (421.1 °C), attributed to the support effect that can inhibit the nitrate salt decomposition. 36 In addition, the band from 200 to 260.1 °C for mesoporous Cr 2 O 3 is attributed to the removal temperature of KIT-6. This result suggests that the introduction of KIT-6 can largely affect the structure Cr 2 O 3 .…”
Section: Resultsmentioning
confidence: 97%
“…It can be clearly found that the weight loss of complete decomposition for the mixed component of KIT-6 and Cr(NO 3 ) 3 is 448.8 °C, which is slightly higher than that of pure Cr(NO 3 ) 3 (421.1 °C), attributed to the support effect that can inhibit the nitrate salt decomposition. 36 In addition, the band from 200 to 260.1 °C for mesoporous Cr 2 O 3 is attributed to the removal temperature of KIT-6. This result suggests that the introduction of KIT-6 can largely affect the structure Cr 2 O 3 .…”
Section: Resultsmentioning
confidence: 97%
“…Low-temperature activity in the NH 3 -SCR has been reported for various catalyst systems, including char-based materials [5,6,7] and zeolites modified with transition metals. [8,9,10] To transition metals catalytically active in the low-temperature reduction of nitrogen oxides belong, among others, copper [9,11,12] and manganese, [13,14,15] used as main catalytically active components or in combinations with other metals, e. g., Cu-Fe, [16] Cu-Ce, [17] Mn-Ce, [18] Mn-Co. [19] Catalytic performance of the NH 3 -SCR catalysts strongly depends on the form and aggregation of catalytically active transition metal species as well as properties of the used catalytic support, such as surface acidity [20] or porosity. [21] Recently, a very promising catalytic performance in the lowtemperature NH 3 -SCR process has been reported for copper modified mesoporous silicas obtained by template ion-exchange (TIE) method.…”
Section: Introductionmentioning
confidence: 99%